Green Human Resource Management dalam Literatur 2021–2025: Analisis Bibliometrik dan Sintesis Tematik - Indri Iswardhani; Sri Astuti Nasir; Nur Fadilah Ayu Sandira (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to provide a comprehensive overview of the development of Green Human Resource Management (Green HRM) research during the 2021–2025 period, while identifying dominant practices, industrial contexts, methodological trends, and research gaps emerging in recent literature. This work employs a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 protocol and structured using the PICOC framework to clarify the analytical boundaries. A systematic search conducted through the Scopus database generated an initial dataset of 200 articles, which was later screened using inclusion–exclusion criteria, resulting in 93 eligible articles for in-depth analysis. The analysis was carried out through two complementary approaches: bibliometric analysis to map publication characteristics and thematic synthesis to identify substantive patterns in GHRM practices, variable relationships, and organizational settings. The findings indicate a significant increase in Green HRM publications during the review period, with a strong predominance of studies originating from Asian countries and service-related industries such as hospitality, banking, healthcare, and manufacturing. The most frequently examined GHRM practices include green training and development, green recruitment and selection, green rewards, and green performance appraisal. Methodologically, more than 70% of the reviewed studies adopt quantitative survey-based approaches using SEM/PLS, while qualitative and mixed-method studies remain limited. Several research gaps were identified, including the lack of longitudinal designs, the dominance of single-country contexts in developing nations, limited exploration of nontraditional industrial sectors, and the need to examine more diverse mediating and moderating mechanisms. These findings provide a strong foundation for shaping a more comprehensive and sustainable future research agenda on Green HRM.